PENGEMBANGAN KELEMBAGAAN PEMASARAN GARAM RAKYAT (Studi Kasus di Desa Lembung, Kecamatan Galis, Kabupaten Pamekasan) - Fauziyah Fauziyah; ihsannudin ihsannudin (Jurnal Sosial Ekonomi Pertanian (J-SEP), 2014)
This research has aimed to (1) determine institutional and marketing channel; (2) marketing margins and farmer's share, and (3)market integration in the salt marketing. The research is conducted in the village of Lembung, Galis sub-district, Pamekasan regency. Analysis methods of this research are descriptive analysis, marketing analysis, and analysis of market integration. The result of this research shows institution has traditional marketing with 2 marketing channels. They are long channel (through wholesalers) and short channel (without going through wholesalers). If we get information from total margin and amount of farmer’s share, second channel  is more efficient than first channel, because total margin of second channel is less than first channel and has more farmer’s share. The value of Integration Market Connection shows salt quality grade 1 and salt quality grade 3 have lower levels of market integration, with IMC value are respectively 1.599, 1.589 (IMC>1). Salt quality grade 2 has a high level of market integration because the value of IMC are -2.383 (IMC<1). Keywords: Development, Marketing, Salt